طوابع الإبل بوادي سوف وتأثيرها في الحياة الاجتماعية و الاقتصادية خلال حقبة الاحتلال الفرنسي (1854-1962م) - الجموعي عثمانيي; رؤوف حفصي; علي أحمد الصالح (University of Eloued جامعة الوادي, 2025)
"تهدف الدراسة في هذا الموضوع إلى تسليط الضوء على طوابع(الوسم) الإبل بوادي سوف وتأثيرها في الحياة الاجتماعية والاقتصادية أثناء فترة الاحتلال الفرنسي (1854-1962م) حيث تمحورت الإشكالية على أشكال الطابع(الوسم) والقبائل الممثلة وتأثيرها في الحياة الاجتماعية والاقتصادية في المنطقة بداية: بفصل تمهيدي تم فيه إبراز اهتمامات أهل وادي سوف بالإبل موضحا الدعوة الربانية للتأمل في الإبل، وتحديد نظم الرعي وأهم المراعي والآبار المخصصة لرعاية أهل المنطقة لإبلهم. الفصل الأول تناول الطابع (الوسم) للحيوانات عند القبائل البدو مبرزا أشكال الطابع والعزائل، وأهم العروش والقبائل المتواجدة في المنطقة وتمثيل طوابع الاعراش و فروعها الممثلة في وادي سوف. وإدراج مجموعة من الصور التوضيحية لهذه الطوابع. تناول الفصل الثاني تأثير طوابع الإبل في الحياة الاجتماعية والاقتصادية، مبرزا دورها في تعزيز التكافل والتواصل الاجتماعي. وتعسف السلطة الاستعمارية في استغلال الإبل وابتزاز ملاكها. ومساهمة قوافل الإبل بوادي سوف في عملية التسليح للثورة. أما الخاتمة احتوت على مجموعة من النتائج التي تم الوصل إليها من خلال هذا العمل ومجموعة من التوصيات المهمة التي تحفظ تراث وتاريخ الأجداد للأحفاد. وتضمنت الملاحق مجموعة من الوثائق والصور نراها مهمة في توضيح بعض نقاط البحث. "The study in this topic aims to shed light on the stamps (marking) camels in oued Souf and their impact on social and economic life during the period of the French occupation ( 1854-1962 ), where the problem centered on the forms of stamp (marking) and tribes represented and their impact on social and economic life in the region Beginning: In an introductory chapter, the interests of the people of oued Souf in camels were highlighted, explaining the divine call to contemplate camels, and identifying grazing systems and the most important pastures and wells dedicated to caring for the people of the region for their camels. The first chapter dealt with the character (marking) of animals among the Bedouin tribes, highlighting the forms of character and isolation, the most important thrones and tribes in the region and the representation of the stamps of the thrones and their branches represented in oued Souf. Include a set of illustrations of these stamps. The second chapter dealt with the impact of camel stamps on social and economic life, highlighting their role in promoting solidarity, social communication and resolving tribal conflicts. The colonial power abuses camels and extorts their owners. And the contribution of camel caravans in oued Souf in the process of arming the revolution. The conclusion contained a set of results reached through this work and a set of important recommendations that preserve the heritage and history of the grandchildren of the ancestors The appendices included a set of documents and photographs that we deem important in clarifying some of the points of research. "
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: الطوابع; الوسم; الإبل; البدو; التأثير في الحياة الاجتماعية والاقتصادية.; stamps; tags; camels; Bedouins; impact on social and economic life